Nitrogen fixation electrode based on carbon nitrogen defect state double-monatomic self-assembly synthesis
The preparation of carbon-nitrogen defective double single atom electrode through the synergistic action of erbium and dysprosium and near-ultraviolet photocatalytic crosslinking method has solved the problems of high energy consumption and insufficient catalyst activity in nitrogen fixation technology, and achieved high-efficiency nitrogen fixation and stability improvement. A better electrochemical nitrogen fixation solution.
Patent Information
- Application Number
- CN202411408605.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The existing nitrogen fixation technology has problems such as high energy consumption, insufficient catalyst activity and selectivity, and environmental pollution, and the stability and catalytic activity of the carbon-nitrogen composite electrode still have room for improvement in electrochemical nitrogen fixation.
Using the synergistic action of erbium and dysprosium, carbon and nitrogen mixed precursors with long-term order structures were prepared by near-ultraviolet photocatalytic cross-linking method to form a carbon and nitrogen defective double single atom self-assembled electrode to improve catalytic activity and stability. And optimize the electrode structure by specific immersion, light irradiation and deposition methods.
It significantly improves the catalytic activity and stability of the electrode, enhances the adsorption and activation ability of nitrogen, inhibits competitive reactions, improves the yield of ammonia and Faraday efficiency, and extends the service life of the electrode.
Smart Images

Figure CN119287429A_ABST
Abstract
Description
1. Technical Field
[0001] The present invention relates to the technical field of electrochemical and environmental functional materials, and in particular to a nitrogen-fixing electrode synthesized based on self-assembly of double single atoms in a carbon-nitrogen defect state and a preparation method thereof. 2. Background Technology
[0002] In the chemical industry, nitrogen fixation technology is the foundation of the entire inorganic chemical industry. Among them, the synthetic ammonia technology was successfully developed by German chemist Fritz Haber in 1909. The Haber-Bosch process with iron as the catalyst was subsequently applied on a large scale in industry, and the catalyst and reaction conditions were continuously improved in the 20th century. However, this technology has the problem of high energy consumption, because the synthetic ammonia reaction needs to be carried out under high temperature and high pressure, resulting in huge energy consumption and high cost; in terms of catalysts, although iron-based catalysts are widely used, their activity and selectivity need to be improved, and they are prone to poisoning and inactivation and need to be replaced or regenerated regularly; at the same time, the hydrogen in the synthesis process mainly comes from the reforming of fossil fuels, which will release a large amount of carbon dioxide, and the discharge of waste gas and wastewater will cause environmental pollution. Urea synthesis technology was first synthesized by German chemist Friedrich Wöhler in 1828 by heating ammonium cyanate. It gradually matured in the 20th century, using ammonia and carbon dioxide as raw materials to react under high temperature and high pressure. However, it faces the problem of harsh reaction conditions. It needs to be carried out under high temperature and high pressure, and has high requirements on equipment materials and manufacturing processes. It has high investment costs and safety risks. The equilibrium conversion rate is low because it is a reversible reaction. The conversion rate is relatively low in actual production, and unreacted raw materials need to be recycled, which increases the complexity and cost of the process. There is also the problem of environmental pollution. Waste gases such as ammonia and wastewater containing pollutants such as ammonia nitrogen during the production process need to be treated before they can meet emission standards.
[0003] Electrochemical nitrogen fixation technology has developed rapidly in recent years. In the late 20th century, as the demand for clean energy and sustainable development increased, electrochemical nitrogen fixation began to attract attention. Early studies focused on exploring suitable electrode materials and reaction conditions. For example, Ding et al. (Angew. Chem. Int. Ed., 2020) explored an example of a bifunctional catalyst that achieved electrocatalytic nitrogen reduction to produce ammonia and nitrogen oxidation to produce nitrate at room temperature, providing a basis for subsequent research. Hao et al. (Small, 2020) found that isolated Pt sites anchored on WO3 nanoplates exhibited the best electrochemical NH3 yield and Faraday efficiency at 0.1 m K2SO4, which were 11 times and 15 times higher than nanoparticles, respectively. Li et al. (ElectrochimicaActa, 2023) proposed a microstructure regulation strategy to improve the electrochemical nitrogen reduction reaction (NRR) performance of carbon-nitrogen composites (CNs) and found that the edge defects of the heptazacyclic ring (C3) are the catalytic active sites of NRR, and CN-Ami exhibits the best NRR performance in terms of activity and selectivity.
[0004] The above research results show that carbon-nitrogen-based composite electrodes have advantages in the field of electrochemical nitrogen fixation, such as providing a large specific surface area to increase active sites, and the synergistic effect between carbon and nitrogen can enhance the catalytic activity; some carbon-nitrogen-based materials have good conductivity and are conducive to electron transport. However, there are also major defects, such as stability needs to be improved, long-term reaction affects performance; catalytic activity is still far from the ideal state. In the future, it is expected that the performance will be further improved by optimizing the structure and composition, and large-scale application will be achieved. The challenges faced include developing efficient and stable synthesis methods, reducing costs, and improving adaptability to complex environments. At the same time, in-depth research on the reaction mechanism is needed to better design and improve the electrode, while improving the efficiency of nitrogen fixation and overcoming existing problems, to provide a better solution for sustainable nitrogen fixation. III. Summary of the invention
[0005] The present invention is made in view of the problems existing in the prior art. In the research and development of carbon-nitrogen composite electrocatalytic nitrogen fixation electrodes, the selection of active centers is crucial. Erbium and dysprosium have unique electronic structures and can form strong interactions with carbon-nitrogen substrates, providing suitable active sites for the adsorption and activation of nitrogen. Secondly, these two metal elements show high catalytic activity in electrochemical nitrogen fixation reactions. By precisely controlling the ratio of erbium and dysprosium, the catalytic performance of the electrode can be optimized. In addition, the synergistic effect of erbium and dysprosium can further improve the stability and durability of the electrode. Compared with other metal elements, erbium and dysprosium have higher selectivity in nitrogen fixation reactions, can effectively inhibit competing reactions such as hydrogen evolution reactions, and improve the yield and Faraday efficiency of ammonia.
[0006] It is an innovative technical idea to introduce near-ultraviolet photocatalytic cross-linking method to prepare carbon-nitrogen mixed precursors with long-period ordered structures to form defect states. This method can introduce a large number of defects in the carbon-nitrogen substrate, thereby increasing the number of active sites and improving the catalytic activity of the electrode. At the same time, by precisely controlling the reaction conditions, the clustering and recrystallization of double single-atom metals can be avoided. The near-ultraviolet photocatalytic cross-linking method is efficient and controllable, and can achieve structural regulation of the carbon-nitrogen substrate under mild conditions. During the reaction, the photocatalyst can promote the cross-linking reaction of the carbon-nitrogen substrate to form a long-period ordered structure. This structure is not only conducive to the dispersion of double single-atom metals, but also can improve the conductivity and stability of the electrode. In addition, by adjusting the type and dosage of the photocatalyst, the performance of the electrode can be further optimized, providing new ideas and methods for the development of electrochemical nitrogen fixation technology.
[0007] In order to achieve the above object, the technical solution of the present invention is a nitrogen-fixing electrode synthesized based on the self-assembly of double single atoms in carbon-nitrogen defect states, characterized in that the preparation method of the electrode comprises the following steps:
[0008] Step 1, selecting a hydrophilic carbon paper with high conductivity and mechanical strength as a substrate, soaking it in dilute nitric acid with a mass concentration of 5%, controlling the reaction temperature to 80°C, and soaking it for 15 minutes to introduce oxygen-containing functional groups and increase the surface roughness, and then soaking it in a sodium hydroxide aqueous solution with a mass concentration of 20% for 5 minutes to adjust the acidity and hydrophilicity of the substrate surface, and finally washing and drying it with deionized water and acetone for multiple times to obtain a pretreated hydrophilic carbon paper substrate;
[0009] Step 2, preparing a sodium hydroxide aqueous solution with a mass concentration of 20%, weighing thiourea dioxide, adding it to the sodium hydroxide aqueous solution to obtain a suspension with a mass concentration of thiourea dioxide of 5%, and stirring it for standby use;
[0010] Step 3, adding a small amount of Eosin Y as a photocatalyst to the thiourea dioxide suspension obtained in step 2, so that the mass concentration of Eosin Y is 0.05%, and continuously stirring for 24 hours under 365nm ultraviolet light irradiation to generate a carbonylation-mediated product sulfoxylate in the thiourea dioxide suspension;
[0011] Step 4, further adding benzaldehyde and 4-vinylpyridine in a molar ratio of 1:2 to the thiourea dioxide suspension after the reaction for 24 hours in step 3, so that the mass concentration of the sum of the two in the solution is 5.7%, and vigorously stirring to produce a jelly. At this time, the stirring speed is reduced, and when the jelly slowly grows until the volume no longer increases, the stirring is stopped to obtain a carbon-nitrogen mixed precursor precipitate with a long-period ordered structure;
[0012] Step 5, transferring the carbon-nitrogen mixed precursor precipitate obtained in step 4 to a mixed solution of hydrogen peroxide and acetonitrile in a mass ratio of 1:4, and vigorously stirring until the carbon-nitrogen mixed precursor precipitate is re-dissociated and presents a colloidal form, retaining a basic sub-micron ordered unit structure;
[0013] Step 6, placing the mixed solution in step 5 under the irradiation of a blue LED light with a wavelength of 450 nm, slowly stirring and adding dropwise a mixed solution of erbium chloride and dysprosium nitrate with a molar ratio of erbium to dysprosium of 3:1 and a mixed mass concentration of 2.5%, until the mixed solution becomes slightly turbid, then stop adding dropwise;
[0014] Step 7, the mixed solution obtained in step 6 is allowed to stand overnight, and when obvious stratification occurs, the supernatant is discarded, and the lower turbid solution is placed in a 10,000Da dialysis bag, and immersed in a sodium hydroxide solution with a mass concentration of 5%. The dialysate is the precursor of the carbon-nitrogen defect state double single atom self-assembled material;
[0015] Step 8, after mixing the precursor of the carbon-nitrogen defect double single atom self-assembly material obtained in step 7 with a Nafion solution with a mass concentration of 5% in equal volumes, a layer of dense carbon-nitrogen defect double single atom composite film is deposited on the surface of the hydrophilic carbon paper substrate obtained in step 1 by constant potential deposition method;
[0016] Step 9, freeze-drying the carbon-nitrogen defect double single atom composite film obtained in step 8, placing it under argon protection, and low-temperature baking at 350°C for 30 minutes to further optimize the distribution of carbon-nitrogen defect states in the composite film and the catalytic active sites of metal atoms, while improving the overall stability of the electrode, thereby obtaining a nitrogen-fixing electrode based on the self-assembly synthesis of carbon-nitrogen defect double single atoms.
[0017] The present invention is beneficial in that:
[0018] 1) By immersing the hydrophilic carbon paper substrate in dilute nitric acid and sodium hydroxide solutions of specific concentrations, oxygen-containing functional groups are introduced, the surface roughness is increased, and the acidity and hydrophilicity are adjusted, providing a good foundation for subsequent steps and enhancing the binding ability of the electrode and the reactant.
[0019] 2) Accurately configure different solutions, use photocatalysts, reactants in a specific molar ratio, and ultraviolet light to generate a carbon-nitrogen mixed precursor precipitate with a long-period ordered structure, ensuring the orderliness and stability of the product structure.
[0020] 3) Accurately control the stirring speed, solution concentration, light wavelength and time, etc. to ensure that the reaction is precisely controllable and improve the quality and consistency of the product.
[0021] 4) The two metal elements of erbium and dysprosium have unique electronic structures and can form strong interactions with the carbon-nitrogen substrate, providing active sites for the adsorption and activation of nitrogen, improving catalytic activity, and the synergistic effect can improve the stability and durability of the electrode. At the same time, it has high selectivity for nitrogen fixation reactions and inhibits competitive reactions.
[0022] 5) By introducing near-ultraviolet photocatalytic cross-linking method to prepare carbon-nitrogen mixed precursors with long-period ordered structures to form defect states, increase the number of active sites, improve electrode catalytic activity, and avoid clustering and recrystallization of double single-atom metals to ensure stable electrode performance.
[0023] 6) After freeze drying and low-temperature calcination, the distribution of carbon and nitrogen defect states and the catalytic active sites of metal atoms in the composite film are further optimized, the overall stability of the electrode is improved, and the service life of the electrode is extended. IV. Description of the drawings
[0024] In order to more clearly illustrate the specific embodiments of the present invention, the drawings used in the description of the specific embodiments are briefly described below.
[0025] Figure 1 This is a spherical aberration-corrected transmission electron microscopy image of the double single atom phase on the nitrogen-fixing electrode synthesized based on the self-assembly of double single atoms in carbon-nitrogen defect states.
[0026] Figure 2 Linear sweep voltammetric curves of nitrogen-fixing electrode synthesized based on self-assembly of double single atoms in carbon-nitrogen defect states and Pt-C and Ni-C electrodes.
[0027] Figure 3 It is the slope of the Tafel curve of the nitrogen-fixing electrode synthesized based on the self-assembly of double single atoms in carbon-nitrogen defect states and the Pt-C and Ni-C electrodes. V. Specific implementation methods
[0028] The present invention is described in detail below with reference to the accompanying drawings and embodiments:
[0029] Embodiment 1:
[0030] A nitrogen-fixing electrode based on the self-assembly synthesis of double single atoms in carbon-nitrogen defect states, the preparation method of the electrode comprising the following steps: first, selecting a hydrophilic carbon paper with high conductivity and mechanical strength as a substrate, soaking it in dilute nitric acid with a mass concentration of 5%, controlling the reaction temperature to 80°C, and soaking it for 15 minutes to introduce oxygen-containing functional groups and increase the surface roughness, then soaking it in a sodium hydroxide aqueous solution with a mass concentration of 20%, soaking it for 5 minutes, adjusting the acidity and alkalinity and hydrophilicity of the substrate surface, and finally washing and drying it with deionized water and acetone for multiple times to obtain a pretreated hydrophilic carbon paper substrate; preparing a sodium hydroxide aqueous solution with a mass concentration of 20%, weighing thiourea dioxide, adding hydrogen A suspension with a mass concentration of 5% of thiourea dioxide is obtained in an aqueous sodium hydroxide solution, and the suspension is stirred evenly for use; a small amount of eosin Y is added to the thiourea dioxide suspension as a photocatalyst to make the mass concentration of eosin Y 0.05%, and the suspension is stirred continuously for 24 hours under ultraviolet light irradiation at 365 nm to generate a carbonylation-mediated product, sulfoxylate, in the thiourea dioxide suspension; benzaldehyde and 4-vinylpyridine are further added in a molar ratio of 1:2 to make the mass concentration of the sum of the two in the solution 5.7%, and the suspension is stirred vigorously to produce a colloid, at which time the stirring speed is reduced, and when the colloid slowly grows until the volume no longer increases, the stirring is stopped to obtain a carbon-nitrogen mixed precursor precipitate with a long-period ordered structure; the obtained The obtained carbon-nitrogen mixed precursor precipitate is transferred to a mixed solution of hydrogen peroxide and acetonitrile in a mass ratio of 1:4, and stirred vigorously until the carbon-nitrogen mixed precursor precipitate is re-dissociated and presents a colloidal form, retaining a basic sub-micron ordered unit structure; the mixed solution is placed under the irradiation of a blue LED light with a wavelength of 450nm, slowly stirred and a mixed solution of erbium chloride and dysprosium nitrate with a molar ratio of erbium to dysprosium of 3:1 and a mass concentration of 2.5% is added dropwise until the mixed solution becomes slightly turbid, and the addition is stopped; the obtained mixed solution is allowed to stand overnight, and obvious stratification occurs, the supernatant is discarded, and the lower turbid solution is placed in a 10,000Da dialysis bag, immersed in a sodium hydroxide solution with a mass concentration of 5%, and dialysis is performed. The precipitate is the precursor of the carbon-nitrogen defect double single atom self-assembly material; the obtained precursor of the carbon-nitrogen defect double single atom self-assembly material is mixed with a Nafion solution with a mass concentration of 5% in equal volumes, and a layer of dense carbon-nitrogen defect double single atom composite film is deposited on the surface of the hydrophilic carbon paper substrate obtained in step 1 by a constant potential deposition method; the obtained carbon-nitrogen defect double single atom composite film is freeze-dried, placed under argon protection, and low-temperature baked at 350°C for 30 minutes to further optimize the distribution of carbon-nitrogen defect states and the catalytic active sites of metal atoms in the composite film, while improving the overall stability of the electrode, thereby obtaining a nitrogen-fixing electrode synthesized based on the carbon-nitrogen defect double single atom self-assembly.
[0031] The nanoparticles on the surface of the electrode were scraped off with a blade, dispersed with ethanol, and analyzed under a spherical aberration-corrected transmission electron microscope. The atomic phase image obtained is shown in the attached figure. Figure 1 As shown, it clearly has a clear double single-atom structure.
[0032] Embodiment 2:
[0033] The electrochemical test was carried out on the nitrogen fixing electrode synthesized based on the self-assembly of double single atoms in carbon-nitrogen defect states obtained by the preparation method described in Example 1.
[0034] A three-electrode system was constructed using a CHI-660D electrochemical workstation produced by Shanghai Chenhua Company to evaluate the nitrogen fixation (NRR) activity of the nitrogen fixation electrode prepared based on the self-assembly synthesis of carbon-nitrogen defect double single atoms. Specifically, the nitrogen fixation electrode was used as the working electrode (WE), the platinum sheet was used as the counter electrode (CE), and the Hg / HgO electrode was used as the reference electrode (RE). -1 Linear sweep voltammetry (LSV) test was performed in an alkaline environment of potassium hydroxide. During the test, the voltage was 5mV s -1 The scan rate was 1000 nm and the linear scan was performed in the range of -0.6 to +0.8 V relative to the reversible hydrogen electrode (RHE). The conversion of the electrode potential relative to the standard hydrogen electrode was based on the formula E RHE =0.098V+pH×0.059V for correction.
[0035] The nitrogen-fixing electrode based on the self-assembly synthesis of carbon-nitrogen defective double single atoms was subjected to linear scanning voltammetry scanning of the electrochemical workstation, and the results are shown in the attached figure. Figure 2 As shown, its hydrogen evolution potential (0.057 V vs. RHE) is significantly better than that of Pt-C and Ni-C electrodes.
[0036] Embodiment 4:
[0037] The electrochemical test was carried out on the nitrogen fixing electrode synthesized based on the self-assembly of double single atoms in carbon-nitrogen defect states obtained by the preparation method described in Example 1.
[0038] The electrochemical workstation and electrode configurations were as in Example 2, and the electrode samples were subjected to electrochemical impedance spectroscopy (EIS) testing to analyze the charge transfer characteristics of the electrode interface. The test was performed at a bias voltage of 250 mV relative to RHE, with a frequency range of 0.1 Hz to 100 kHz and a fixed amplitude of 10 mV.
[0039] From the Tafel diagram, we can see that (see Appendix Figure 3 ), the Tafel slope of the nitrogen-fixing electrode based on the self-assembly synthesis of carbon-nitrogen defective double single atoms prepared in Example 1 is 44.1 mV dec -1, which is much lower than the Tafel slope of Pt-C and Ni-C electrodes (65.27 mV dec). -1 and 95.25mV dec -1 , indicating that the catalyst active layer has higher charge transfer efficiency than traditional Pt-C and Ni-C electrodes.
[0040] Embodiment 5:
[0041] The electrochemical nitrogen fixation yield was tested using the nitrogen fixation electrode synthesized based on the self-assembly of double single atoms in carbon-nitrogen defect states obtained by the preparation method described in Example 1.
[0042] Electrocatalytic reduction of nitrogen was also carried out in the electrochemical workstation, electrode and electrolyte environment as in Example 2. The nitrogen-fixing electrode (4×4 cm 2 ) was placed at the bottom of the electrolytic cell, a counter electrode (Pt) of area was added to the top of the electrolytic cell, and 70 mL of 1.0 mol L -1 Potassium hydroxide was used as the electrolyte. The NRR operation was performed using a chronoamperometry electrochemical workstation with a current density of 5 mA cm -2 Before the NRR experiment, the dissolved oxygen was removed by vacuum pumping for 10 min, and then high-purity nitrogen (99.999%) was used at a rate of 100 mL min -1 The flow rate was purged for 60 minutes to obtain a saturated nitrogen water suspension. During the illumination process, the flow rate was continued at 3 mL min -1 Nitrogen was introduced into the reaction solution at a flow rate of , and samples were taken at regular intervals and analyzed by Nessler's reagent colorimetry and ion chromatography. In addition, the Watt & Chrisp method was used to determine whether hydrazine (N2H4) was produced in the product. The specific method was as follows: 5 mL of the reaction solution was mixed with 5 mL of a color developer (mixed with 5.99 g of p-(dimethylamino)benzaldehyde, 30 mL of concentrated hydrochloric acid, and 300 mL of ethanol), and after 10 minutes, the absorbance of the resulting solution was measured at a wavelength of 455 nm.
[0043] The results show that at 5 mA cm -2 At a current density of 2.5 Å, the yield of synthetic ammonia was 284.2 nmol cm -2 h -1 , no N2H4 is produced, and the Faradaic efficiency (FE) is 85.2%.
[0044] Embodiment 6:
[0045] The electrochemical nitrogen fixation yield was tested using the nitrogen fixation electrode based on the self-assembly synthesis of carbon-nitrogen defective double single atoms obtained by the preparation method described in Example 1. The specific experimental conditions were the same as those in Example 5, but the current density was adjusted to 10 mA cm -2At a current density of , the yield of synthetic ammonia is 522.17 nmol cm -2 h -1 , no N2H4 is produced, and the Faradaic efficiency (FE) is 74.2%.
[0046] Embodiment 7:
[0047] The electrochemical nitrogen fixation yield was tested using the nitrogen fixation electrode based on the self-assembly synthesis of carbon-nitrogen defective double single atoms obtained by the preparation method described in Example 1. The specific experimental conditions were the same as those in Example 5, but the current density was adjusted to 15 mA cm -2 At a current density of , the yield of synthetic ammonia is 658.49 nmol cm -2 h -1 , no N2H4 is produced, and the Faradaic efficiency (FE) is 65.23%.
[0048] The specific implementation methods described above are only used to specifically illustrate the spirit of the present invention, and the protection scope of the present invention is not limited thereto. For those skilled in the art, other implementation methods can certainly be easily made by changing, replacing or modifying the technical contents disclosed in this specification, and these other implementation methods should all be covered within the protection scope of the present invention.
Claims
1. A nitrogen-fixing electrode synthesized based on the self-assembly of double single atoms in carbon-nitrogen defect states, characterized in that: The preparation method of the electrode comprises the following steps: Step 1, selecting a hydrophilic carbon paper with high conductivity and mechanical strength as a substrate, soaking it in dilute nitric acid with a mass concentration of 5%, controlling the reaction temperature to 80°C, and soaking it for 15 minutes to introduce oxygen-containing functional groups and increase the surface roughness, and then soaking it in a sodium hydroxide aqueous solution with a mass concentration of 20% for 5 minutes to adjust the acidity and hydrophilicity of the substrate surface, and finally washing and drying it with deionized water and acetone for multiple times to obtain a pretreated hydrophilic carbon paper substrate; Step 2, preparing a sodium hydroxide aqueous solution with a mass concentration of 20%, weighing thiourea dioxide, adding it to the sodium hydroxide aqueous solution to obtain a suspension with a mass concentration of thiourea dioxide of 5%, and stirring it for standby use; Step 3, adding a small amount of Eosin Y as a photocatalyst to the thiourea dioxide suspension obtained in step 2, so that the mass concentration of Eosin Y is 0.05%, and continuously stirring for 24 hours under 365nm ultraviolet light irradiation to generate a carbonylation-mediated product sulfoxylate in the thiourea dioxide suspension; Step 4, further adding benzaldehyde and 4-vinylpyridine in a molar ratio of 1:2 to the thiourea dioxide suspension after the reaction for 24 hours in step 3, so that the mass concentration of the sum of the two in the solution is 5.7%, and vigorously stirring to produce a jelly. At this time, the stirring speed is reduced, and when the jelly slowly grows until the volume no longer increases, the stirring is stopped to obtain a carbon-nitrogen mixed precursor precipitate with a long-period ordered structure; Step 5, transferring the carbon-nitrogen mixed precursor precipitate obtained in step 4 to a mixed solution of hydrogen peroxide and acetonitrile in a mass ratio of 1:4, and vigorously stirring until the carbon-nitrogen mixed precursor precipitate is re-dissociated and presents a colloidal form, retaining a basic sub-micron ordered unit structure; Step 6, placing the mixed solution in step 5 under the irradiation of a blue LED light with a wavelength of 450 nm, slowly stirring and adding dropwise a mixed solution of erbium chloride and dysprosium nitrate with a molar ratio of erbium to dysprosium of 3:1 and a mixed mass concentration of 2.5%, until the mixed solution becomes slightly turbid, then stop adding dropwise; Step 7, the mixed solution obtained in step 6 is allowed to stand overnight, and when obvious stratification occurs, the supernatant is discarded, and the lower turbid solution is placed in a 10,000Da dialysis bag, and immersed in a sodium hydroxide solution with a mass concentration of 5%. The dialysate is the precursor of the carbon-nitrogen defect state double single atom self-assembled material; Step 8, after mixing the precursor of the carbon-nitrogen defect double single atom self-assembly material obtained in step 7 with a Nafion solution with a mass concentration of 5% in equal volumes, a layer of dense carbon-nitrogen defect double single atom composite film is deposited on the surface of the hydrophilic carbon paper substrate obtained in step 1 by constant potential deposition method; Step 9, freeze-drying the carbon-nitrogen defect double single atom composite film obtained in step 8, placing it under argon protection, and low-temperature baking at 350°C for 30 minutes to further optimize the distribution of carbon-nitrogen defect states in the composite film and the catalytic active sites of metal atoms, while improving the overall stability of the electrode, thereby obtaining a nitrogen-fixing electrode based on the self-assembly synthesis of carbon-nitrogen defect double single atoms.